Fred Dibnah's : Made in Britain - Hall, David (London Bantam Press, 2010)
Takes us on a journey that took the author to Britain's most iconic engineering marvels as well as less familiar sites: from the Forth Bridge and the Middlesbrough Transporter Bridge to Europe's last deep-working iron ore mine in Cumbria and a local castings workshop in Bo'ness.
Include Illustrations and Index
Keywords: Traction-Engines